Following the Life-Cycle of Base-Ring Female Figurines in Late Bronze Age Cyprus - Alexandrou, Constantina (Trinity College (Dublin, Ireland). Department of Classics, 2016)
This research investigates the Late Cypriot II–IIIA or Base-Ring female terracotta figurines from the moment they were just a lump of clay until their death/discard aiming to get fresh insights on their use, role, character and significance. Consequently, the whole thesis is based on the so-called biographical approach. The different stages of the figurines’ life-cycle are examined through bringing together a variety of approaches, theoretical frameworks and methodologies. The present thesis starts with an introduction to the basic elements characterising the Late Bronze Age in Cyprus. The history of research, traditional approaches and interpretations on this group of figurines are then presented. Matters of provenance and dating are discussed in the final sections of Chapter I. Chapter II investigates the first stages of the terracottas’ life-cycle; elements related to their conception and manufacture are presented here. More precisely, the creation of a more thorough typology is attempted while the sequences followed for their production are established. Through these two aspects it was possible to identify features constituting deliberate and conscious choices of the artisans that could be connected with the use, character and role of these figurines. This investigation uses primary and secondary sources, as well as experimental and experiential approaches. Foreign influences, influences from figurines rendered in other materials as well as continuities with the previous local tradition in terms of their typologies and manufacturing procedures are also discussed and evaluated in this chapter. Chapter III deals with questions related to workshops and figurine-makers. Firstly, this chapter attempts to identify individual hands/workshops through certain features/details characterising the typology and manufacturing procedures (‘motor habits’) of the figurines. The evidence from the application of the portable X-ray Fluorescence on the material from Enkomi is presented next. The aim of this study is firstly to identify any possible imports from other sites and most importantly to explore the possibility that the different types were produced in different workshops. The third aspect examined is the identity of the figurine-makers; primary and secondary sources on the female and zoomorphic figurines and pottery are used for this investigation. The role and experience of the artisans in the figurine-making procedure is then explored, drawing on the evidence provided by case-studies using anthropological and ethnoarchaeological approaches. Chapter IV examines the exact archaeological context of the terracottas in the three contexts of their discovery (settlements, burials and ritual spaces). Contextualisation required the following data collection: a description of the exact place and character of the place they were found, other finds discovered together with the figurines (i.e. assemblages) and the state of their preservation at the time of their deposition (i.e. fragmentation). The goal of this approach is to observe patterns in order to develop a more robust analysis of their use(s)/depositional practices in the different contexts. Finally, Chapter V investigates the Base-Ring female figurines in their longue durée. More precisely, this chapter explores the potential reasons that led to the Base-Ring female figurines’ production through a typological and contextual (social and archaeological) comparison with the ‘plank-shaped’ and ‘transitional’ figurines of the end of the Early Bronze Age–beginning of Late Bronze Age. At the same time it investigates the possible reasons that led to their decline, also through a typological and contextual comparison with the so-called ‘goddesses with the upraised arms’ which gradually replaced the Base-Ring specimens in the Late Cypriot IIIB. Lastly, these figurines are examined in relation to the zoomorphic and male terracottas produced during the Late Bronze Age.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin